Deterministic finite capacity automata: a solution to reduce the complexity of modeling and control of automated manufacturing systems - Qiu, R.G.; Joshi, S.B. (1996 IEEE International Symposium on Computer-Aided Control System Design, 1996)
The solution complexity of a synthesized control model of an automated manufacturing system grows exponentially in the number of constituent components in the system (Ho, 1992), thus resulting in the control model being either theoretically untractable in computation (Ramadge, 1989) or practically unfeasible in implementation. By taking advantage of both Petri nets and supervisory control theory, this paper presents a new methodology, called deterministic finite capacity automaton, which when used to model the control of an automated manufacturing system can significantly reduce model complexity. By taking into account the nature of manufacturing automation and combining the technology advances in multiprocessing systems, an automaton-based control model capable of running coordinated computing processes is defined. An adjustable language is introduced into the control model, to make it function more efficiently.